Study Invasive Mollusks Melanoides tuberculata and Achatina fulica in District Labuhan Batu Selatan - Arman Harahap (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
District Labuhanbatu selatan has natural/artificial inland waters for various usages. For example, freshwater has supported various activities such as agriculture, plantations, inland fisheries, and ecotourism. This study reports the presence of invasive mollusk in freshwater (Melanoides tuberculata) and terrestrial (Achatina fulica) habitats. This study is the first report regarding the spatial distribution of the three invasive mollusk species in the inland waters of District Labuhanbatu selatan. These invasive mollusks species are a severe threat to the preservation of native species and human health because they are an intermediate host for several types of parasites, such as the trematode group. The spreading and rapid development of these invasive mollusks is caused by their reproductive ability and resistance to poor environmental quality and airborne dispersal factors by birds, water flow, and commercial activities. This invasive species can directly cause huge economic losses as they become a pest inagricultural activities, plantations, and freshwater fisheries (aquaculture). They also can transmit pathogens and displacement of native species. Therefore, it is recommended to have a preventive effort to tackle the expansion of in District Labuhanbatu selatan.